FACTORS THAT AFFECT THE PERFORMANCE OF EMPLOYEES OF PT TELKOM INDONESIA WITEL SOLO - Aurora Noel Saputri; Arif Nugroho Rachman (STEKOM PRESS, 2022)
Observations that contain the intent to determine how much influence the variable understanding of SIA, compensation, competence, motivation, experience on the performance of employees of PT. Telkom Indonesia Witel Solo. The population contained in this study amounted to 70 employees with sample criteria targeting employees who use accounting information systems totaling 42 employees. The tool to analyze the data is multiple regression analysis. With the results of the partial research test where the variables of understanding accounting information systems, compensation, and work experience have no significant effect on employee performance, while competence and work motivation affect employee performance. And the results of the simultaneous test of all these variables together have a significant effect on employee performance.